2003
DOI: 10.1002/mds.10574
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopamine transporter imaging in the diagnosis of atypical tremor disorders

Abstract: Dopamine transporter (DAT) imaging detects presynaptic dopamine neuronal dysfunction and thereby assists differentiation of conditions with and without dopamine deficit. In atypical tremor disorders, DAT imaging can differentiate between Parkinson's disease (PD), where dopamine deficit is demonstrated on DAT imaging, and essential tremor, where no dopamine deficit is found. DAT imaging may be particularly informative in monosymptomatic rest tremors, benign tremulous Parkinson's syndrome, and in the elderly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 20 publications
0
27
0
3
Order By: Relevance
“…Reports on DAT binding in vascular PS provide heterogeneous results, which might indicate that vascular PS is a mixed entity that is not yet well characterized (40). Some authors have reported normal or only a slight but insignificant reduction of DAT binding in patients with suspected vascular PS (45,54,55); others have found significantly reduced binding values (56,57). This discrepancy may be attributed to differences in patient populations and the relatively small numbers of subjects investigated.…”
Section: Vascular Psmentioning
confidence: 99%
“…Reports on DAT binding in vascular PS provide heterogeneous results, which might indicate that vascular PS is a mixed entity that is not yet well characterized (40). Some authors have reported normal or only a slight but insignificant reduction of DAT binding in patients with suspected vascular PS (45,54,55); others have found significantly reduced binding values (56,57). This discrepancy may be attributed to differences in patient populations and the relatively small numbers of subjects investigated.…”
Section: Vascular Psmentioning
confidence: 99%
“…Singlephoton emission computerized tomography (SPECT) of the dopamine transporter (DAT) as a marker for nigrostriatal neuronal degeneration has been proven useful and feasible in the differential diagnosis of PD and essential tremor (ET) in numerous studies [1][2][3][4][5][6][7][8][9][10][11] with a sensitivity of up to 97% and a specificity of 100% [3,6]. Furthermore, DAT SPECT is able to detect preclinical ipsilateral reduction of DAT density in patients with hemiparkinsonism [7,8], whereas ET and dystonic tremor is defined by normal DAT density [12].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging of the presynaptic DAT has evolved into an important diagnostic tool for patients with Parkinsonian syndromes [1, [23][24][25], and thus has become a routine clinical procedure. Visual assessment of DAT SPECT studies in many cases enables clinicians to decide whether neurodegeneration of presynaptic neurons has occurred and to confirm or exclude a neurodegenerative Parkinsonian syndrome [2].…”
Section: Discussionmentioning
confidence: 99%